Cervical cancer - risk factors, prevention and diagnostic procedures in HPV infections and cervical carcinoma. Epidemiological analysis of morbidity and mortality in Poland and the world in 2012-2018 - Kinga Ruszel; Piotr Pokorski; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2019)
The following article is an analysis of current literature and the epidemiology of cervical cancer in Poland and the rest of the world over the 2012-2018 period. The analysis is based on reference articles and epidemiological reports from WHO - Cancer Mortality Database, The European Cancer Observatory, The Global Cancer Observatory (Globocan) and from the National Cancer Registry as well as statistical data on HPV vaccination based on the article "Szczepienia ochronne w Polsce" from the Polish National Hygiene Institute (PZH). Additional information on HPV infections, clinical manifestation, diagnostic procedures, treatment and the state of HPV vaccination was sourced from publications found on databases such as: PubMed, Medline and Google Scholar. The increasing accessibility of a variety of sources concerning cervical cancer correlates with an increase in the frequency of gynaecological visits and cytological screenings attended by women. A successful decrease in morbidity and mortality due to HPV infections, which are the cause of cervical cancer and head and neck cancers may lead to the inclusion of HPV vaccination into the national vaccination program. Spreading awareness about the risk amongst young adults and parents, protecting their children through vaccination is necessary in order to achieve a decrease in morbidity and mortality due to cervical cancer.